2018
DOI: 10.3389/fcimb.2018.00323
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia pseudotuberculosis BarA-UvrY Two-Component Regulatory System Represses Biofilms via CsrB

Abstract: The formation of biofilms by Yersinia pseudotuberculosis (Yptb) and Y. pestis requires the hmsHFRS genes, which direct production of a polysaccharide extracellular matrix (Hms-ECM). Despite possessing identical hmsHFRS sequences, Yptb produces much less Hms-ECM than Y. pestis. The regulatory influences that control Yptb Hms-ECM production and biofilm formation are not fully understood. In this study, negative regulators of biofilm production in Yptb were identified. Inactivation of the BarA/UvrY two-component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…By contrast, RcsB amounts were the same for both wild-type Salmonella and the csrB csrC double mutant in LB broth without NaCl (S7A Fig), which is in contrast to previous findings reported with Yersinia pseudotuberculosis [33], and this was also the case for RcsD amounts (S7B Fig). Cumulatively, the results in this section strongly suggest that when wild-type Salmonella experiences low osmolarity, BarA activates RcsB-dependent transcription by reducing RcsC abundance through the action of the SirA-dependent CsrB and CsrC regulatory RNAs.…”
Section: Bara Activates Rcsb Via the Sira-activated Regulatory Rnas Ccontrasting
confidence: 94%
See 1 more Smart Citation
“…By contrast, RcsB amounts were the same for both wild-type Salmonella and the csrB csrC double mutant in LB broth without NaCl (S7A Fig), which is in contrast to previous findings reported with Yersinia pseudotuberculosis [33], and this was also the case for RcsD amounts (S7B Fig). Cumulatively, the results in this section strongly suggest that when wild-type Salmonella experiences low osmolarity, BarA activates RcsB-dependent transcription by reducing RcsC abundance through the action of the SirA-dependent CsrB and CsrC regulatory RNAs.…”
Section: Bara Activates Rcsb Via the Sira-activated Regulatory Rnas Ccontrasting
confidence: 94%
“…CsrB and CsrC act by sequestering CsrA, an RNA-binding protein that binds to the 5' untranslated region (UTR) of hundreds of transcripts, typically decreasing their translation [29][30][31][32]. That BarA activation of RcsB may be mediated by CsrB and CsrC in Salmonella is also supported by the phenotype of a csrB mutant Yersinia pseudotuberculosis grown on solid media, which produced 8-fold less RcsB protein than the wild-type strain [33].…”
Section: Bara Activates Rcsb Via the Sira-activated Regulatory Rnas Cmentioning
confidence: 99%
“…Surprisingly, while the phosphorelay activity of BarA was not required for S. algae biofilm formation on the abiotic surface, phenotypic differences in biofilm formation patterns were recorded upon the expression of mutants in two or all three amino acids in the phosphorylation cascade. Notably, control of biofilm cohesiveness by BarA has been reported in Y. pseudotuberculosis (Schachterle et al, 2018). A limitation of our study is the strong plasmid effect, which altered dramatically the biofilm phenotypes under investigation, as well as the intrinsic difficulty of performing gene manipulation in this strain.…”
Section: Discussionmentioning
confidence: 94%
“…Interruption of the hybrid sensor histidine kinase barA caused significant inhibition of biofilm formation. A study in Yersinia pseudotuberculosis showed a barA mutant to increase CR binding while surface-associated biofilm in multiwell plates was not significantly different from that of the WT (Schachterle et al, 2018). Surprisingly, while the phosphorelay activity of BarA was not required for S. algae biofilm formation on the abiotic surface, phenotypic differences in biofilm formation patterns were recorded upon the expression of mutants in two or all three amino acids in the phosphorylation cascade.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested colony morphology and binding of the diazo dye, Congo red, to visualize differences in curli and PGA production by these strains. [58][59] Colonies of wt, pga and crl strains were red in color (Panel D) indicative of binding of Congo red to both PGA and crl, while the cla and epsstrains did not bind the dye. To compare the viscosity of bacterial suspensions and biofilms we measured viscosity curves (Fig.…”
Section: Resultsmentioning
confidence: 99%